Monocytosis in primary care and risk of haematological malignancies. (16th December 2022) - Christensen, Mathilde Egelund; Siersma, Volkert; Kriegbaum, Margit; Lind, Bent Struer; Samuelsson, Jan; Østgård, Lene Sofie Granfeldt; Grønbæk, Kirsten; Andersen, Christen Lykkegaard
Abstract: Monocytosis (≥0.5 × 10 9 /L in peripheral blood) is the hallmark of chronic myelomonocytic leukaemia (CMML) but may be present in a spectrum of diseases including other haematological malignancies. In the primary care sector, monocytosis is a relatively common finding, but its predictive value for haematological malignancy is unknown. We included 663 184 adult primary care patients from the greater Copenhagen area with one or more differential cell counts registered between 2000 and 2016 and followed them in the extensive nationwide Danish health data registers for 3 years after blood sampling. We used logistic regression to model the risk of haematological malignancy and death following monocytosis. Monocytosis was associated with an increased risk of all types of haematological malignancy with the greatest relative risk increase observed in CMML with an OR of 105.22 (95% confidence interval: 38.27–289.30). Sustained monocytosis (at least two requisitions in 3 months) further increased CMML risk, although the diagnosis was still very rare, that is, observed in only 0.1% of these individuals. Outside the haematological setting, the absolute risk of haematological malignancy associated with monocytosis is low and haematological malignancy should mainly be suspected when monocytosis is sustained or the clinical presentation raises suspicion of malignancy.